Oskar Fischinger visual music - Fischinger, Oskar 1900-1967 (Center for Visual Music, 2017)
A collection of abstract animated films by Oskar Fischinger, master of "absolute" or non-objective filmmaking. Using geometric patterns and shapes choreographed tightly to classical music and jazz, he created what are called visual music films
Bonus features: Pierrette I, 1924-26, 1920s-30s home movies and experiments, Berlin (black and white), squares fragment (1934) and various 1930s color animation tests
Keywords: Film; DVD-Video